Phytochemical Profile and In Vitro Antioxidant and Photobiological Properties of Different Extracts from Prangos ferulacea Lindl. - Mariangela Marrelli; Francesca Giordano; Maria Rosaria Perri; Valentina Amodeo; Noemi Baldino; Carmine Lupia; Dimitar Uzunov; Vincenzo Musolino; Filomena Conforti; Maria Luisa Panno (MDPI AG, 2023)
Interesting photobiological properties have been demonstrated for some Cachrys species, including C. libanotis L., C. sicula L., and C. pungens Jan. The present study was designed to assess the photocytotoxic activity of Prangos ferulacea Lindl. (synonym of C. ferulacea (L.) Calest.). This plant was previously considered a Cachrys species but, at present, it is part of the Prangos genus. P. ferulacea is an orophilous plant present in the eastern Mediterranean and in western Asia. Three different extraction techniques were utilized. Obtained extracts were compared both for their phytochemical content and for their photobiological properties on human melanoma cells irradiated with UVA light. The apoptotic responses, together with the antioxidant activity, were also assessed. P. ferulacea extracts were able to affect cell viability in a concentration-dependent manner, with the sample obtained through supercritical CO2 extraction showing the highest activity (IC50 = 4.91 μg/mL). This research points out the interesting content in the photoactive compounds of this species, namely furanocoumarins, and could provide a starting point for further studies aimed at finding new photosensitizing agents useful in cancer photochemotherapy.